(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article presents the results of the analysis of the impact of the crisis in Ukraine on the export of Russian weapons. Special attention is paid to the supply of weapons to the countries of Southeast Asia. The prospects of cooperation between Russia and sub-Saharan Africa and Iran are also outlined.